The Use of Aeration Technology Based on Solar energy to Improve Water Quality and Increase fish Growth Rate in Net Cages Telaga Batu Arang Reservoir - Kahar; Anisum; Rudiyanto (Jurnal Magrobis, 2022)
The research aims to determine the effect of the aeration system for floating net cages sourced from solar energy on water quality and fish prductivity in the Talaga Batu Arang reservoir. The method used factorial randomized block design with the first factor being the location of the cage to the venturi pump and the second being the diameter of the venturi pump. The results showed that the plots afected by the venturi pump were higher at 160,05% compared to those using the venturi pump which was 134.16%. While those not given aeration at 118,61%.